Effect of drying different inclusion plasters on the mechanical properties of thermoactivated acrylic resins - de Arruda Paes, Tarcisio José [UNESP]; Rossi, Natália Rivoli [UNESP]; de Carvalho, Tayná Mendes Inácio [UNESP]; Macedo, Vanessa Cruz [UNESP]; de Sá dos Santos Gomes, Michelle [UNESP]; Nakano, Leonardo Jiro Nomura [UNESP]; Inagati, Cristiane Mayumi [UNESP] (FapUNIFESP (SciELO), 2021)
This article aimed to evaluate some mechanical and chemical properties of acrylic thermoactivated resins by microwave energy, varying the condition and type of plaster. The groups were divided into Lucitone and Vipi-Wave groups, with or without previous treatment (drying) of type III and IV plasters. It was evaluated flexural strength, microhardness, roughness, porosity, residual monomer, and also, time and temperature relationship of plaster and acrylic resin during the polymerization cycles. The data were analyzed using Analysis of Variance (ANOVA) 5%, followed by Tukey's test. The results showed that the drying of the plaster influenced the results and the groups with dry plaster maintained a higher temperature permanence. Therefore, changes in the water condition contained in the inclusion plaster showed effects on the final properties of the acrylic resin, which may be a technical indicator for laboratory procedures in the manufacture of prosthetic devices.
Keywords: Acrylic resin; Dental plaster; Flexural strength; Hardness; Roughness